Statistics of general morbidity and mortality from non-neoplastic diseases of the thyroid gland in iodine-deficient regions located within the zone of radioactive contamination (using the Penza region as an example) - N. O. Tsyplikhin; E. V. Komarova; M. G. Fedorova; V. S. Vasiliev (Сибирский научный медицинский журнал)
Thyroid diseases occupy one of the leading places in the world among all non-neoplastic diseases of the endocrine system. This problem is also relevant in the Russian Federation, their prevalence depending on the region ranges from 35 to 60 %.   Aim of the study was to investigate the structure of morbidity and mortality from thyroid diseases in iodinedeficient regions located within the zone of radioactive contamination using the Penza region as an example.   Material and methods. The data of the regional information and analytical medical system ProMed were analyzed. Overall morbidity was studied from January to April 2024, mortality – from 2019 to 2024.   Results. 89.70 % of cases were registered in women of all age categories, and only 10.30 % in men. The thyroid diseases were mainly diagnosed in elderly people (36.41 % of cases). Their structure is specific for age categories: among persons under 18 years of age, “other specified thyroid diseases” were most often registered (31.67 % of cases), in the age group from 18 to 44 years – “unspecified thyroid disease” (25 %), among patients aged 45 to 90 years – nontoxic multinodular goiter (28.65 % of cases in middle-aged individuals, 35.2 % among the elderly and 29.55 % – among the seniors). Mortality from thyroid diseases is extremely rare, but in some cases, thyroid diseases were indicated in the “other important conditions” column of the death certificate, therefore, pathological conditions of the gland make a significant contribution to the development of thanatogenesis.   Conclusions. The gender and age distribution of thyroid diseases was established; they predominate in women in all age categories, the elderly are at risk. Mortality due to this category of diseases is rare. At the same time, the development of both hypo- and hyperthyroidism negatively affects the functioning of a number of organs and systems of the body, which can make a significant contribution to the development of thanatogenesis. The number of registered cases of thyroid diseases in the region generally corresponds to the general statistical data for the Russian Federation.